Advances in the research of celery, an important Apiaceae vegetable crop. (17th February 2018) - Li, Meng-Yao; Hou, Xi-Lin; Wang, Feng; Tan, Guo-Fei; Xu, Zhi-Sheng; Xiong, Ai-Sheng
Abstract: Celery ( Apium graveolens L.), one of the most important vegetables in Apiaceae family, is cultivated worldwide and utilized in food and cosmetic industries because it is an excellent source of vitamins, phenolic compounds, volatile oils and other nutrients. Celery extracts possess various medicinal properties, such as antibacterial, anti-inflammatory and lowering blood glucose and serum lipid levels. With the rapid advancements in molecular biology and sequencing technology, studies on celery have been performed. Numerous molecular markers and regulatory genes have been discovered and applied to improve celery. Research advances, including genetic breeding, genomics research, function genes and chemical composition, regarding celery are reviewed in this paper. Further exploration and application trends are briefly described. This review provides a reference for basic and applied research on celery, an important Apiaceae vegetable crop.